Effects of dietary iron supplementation on growth performance, fatty acid composition and fatty acid metabolism in rainbow trout (Oncorhynchus mykiss) fed vegetable oil based diets - Shyamalie Sendadheera; Giovanni Turchini; Thanongsak Thanuthong; David Francis (2012)
Effects of dietary iron supplementation on growth performance, fatty acid composition and fatty acid metabolism in rainbow trout (Oncorhynchus mykiss) fed vegetable oil based diets